O projeto Viação Paraíba e a interiorização do cinema paraibano uma análise dos processos de produção dos filmes de seus egressos - Araújo, Josemary Macedo da Silva (2021)
From the identification of the territorial scope of cinema actions and the propulsion of film productions from cities in the interior of Paraíba, this research proposes to investigate the process of interiorization of Paraíba cinema, delimiting itself to the ViAção Paraíba project, as it understands its relevance in terms of scope and regularity, presenting its modes of action and investigating how it contributes to cinema in the state. For this, we used quantitative and qualitative methods in an exploratory and descriptive research, considering data collection through structured and semi-structured interviews between the main actors, such as graduates and staff; documentary and bibliographic research; field diaries; and procedural analysis of filmmaking. The chapters are divided into three, where in the first we provide a historical contextualization of Paraíba's cinema; in the second, we present the ViAção Paraíba project and its main development action, Jabre - Laboratório Paraibano para Jovens Roteiristas; and, in the last one, we analyzed the construction processes of the short films produced by its graduates, demarcating as a premise ex-participants who have integrated the two actions. We use the theory of Bill Nichols (2005) and Jullier & Marie (2009), as an apparatus for the analysis of audiovisual language, and the precepts of the networks of creation proposed by Cecília Almeida Salles (2018) to analyze the construction process of the films made by these young people and identify how ViAção Paraíba contributes not only to the process of interiorization of cinema in Paraíba, but also to the ways of making films and their results.